Design, Synthesis and Biological Evaluation of Novel Thienylpyridyl- and Thioether-Containing Acetamides and Their Derivatives as Pesticidal Agents - Li, Huan; Yang, Na; Xiong, Lixia; Wang, Baolei (Molecules (Basel, Switzerland), 2021)
Referring to the structural information of the “hit” compound A from the reported pharmacophore-based virtual screening, a series of novel thienylpyridyl- and thioether/sulfoxide/sulfone-containing acetamide derivatives have been designed and synthesized. The structures of new compounds were confirmed by 1H NMR, 13C NMR and HRMS. The single-crystal structure of A was firstly reported. All the new synthesized compounds were evaluated for insecticidal activities on Mythimna separata Walker and Plutella xylostella L. Through a step-by-step structural optimization, the high insecticidal agents, especially towards Plutella xylostella L., have been found, and thienylpyridyl- and sulfone/thioether-containing acetamides Iq, Io, Ib and A, which are comparable with the control insecticides cartap, triflumuron and chlorantraniliprole in the present study, can be used as novel lead structures for new insecticides innovation research. In addition, some of the compounds, e.g., A, Ih, Id, Io and Iq, also exhibited favourable fungicidal activities against Physalospora piricola, Rhizoctonia cerealis and Sclerotinia sclerotiorum and would provide useful guidance for the design and development of new fungicides.